Penggunaan jamur merang (Volvariella volvacea) sebagai bahan peningkat nilai gizi dan organoleptik pada produk nugget - Dwiani, Afe; Rahman, Suburi; Waris, Abdul (Universitas Muhammadiyah Mataram, 2024)
Nugget is a highly nutritious chicken product, especially protein, but lacks fibre. The addition of other ingredients, namely fibre-rich merang mushrooms, is expected to increase the fibre content, which is lacking in nugget products, and maintain the protein nutrition and organoleptics. This study aims to determine the effect of substituting Merang mushroom on the chemical and organoleptic nutritional value of nuggets. This study used RAL with 5 treatments, namely N1 (0% Merang mushroom substitution), N2 (25% Merang mushroom substitution), N3 (50% Merang mushroom substitution), N4 (75% Merang mushroom substitution) and N5 (100% Merang mushroom). The results obtained were analysed with analysis of variance at the 5% level using SPSS 15.0. Significantly different results were tested using the Tukey test. The results showed that the nuggets with Merang mushroom substitution that complied with SNI 6683-2014 and was the best treatment based on chemical quality (moisture content, protein content and crude fibre) and hedonic organoleptic (colour, aroma, taste and texture) was treatment N2 (25% Merang mushroom substitution), which produced 59. 66% moisture content; 9.22% protein content; 17.67% fibre content, with a colour score of 3.75 (criteria like); aroma 3.65 (criteria like); taste 3.30 (criteria somewhat like) and texture 3.60 (criteria like).